The Promises and Perils of Technological Solutions to the Troubles with Capital Punishment. Issue 3 (August 2021) - Linders, Annulla; Kansal, Shobha Pai; Shupe, Kyle; Oakley, Samuel
In this article, we interrogate the entanglement of technology with the moral dilemmas of capital punishment in the United States. Although death is obviously front and center of capital punishment, it is often backgrounded analytically speaking, serving as a looming backdrop that rarely makes it to the center of analysis. For the purposes of this article, however, death is an important focal point precisely because it is the direct target of execution technology and also the most crucial element implicated when something goes wrong with executions. Using the introduction of new execution technology (the electric chair, the gas chamber, and lethal injection) in every state as our empirical case, we enhance our understanding of the promises and perils of new execution technology by showing how the boundaries between acceptable and unacceptable executions get redrawn with each new technology, thus undermining the prospects of a technological solution to the dilemmas with capital punishment. We argue that technology cannot fix capital punishment and that is because the problem, at its root, is not about how efficiently and painlessly we kill but instead the fact that we kill at all. And this, we conclude, is a moral, not technological, problem.